2021
DOI: 10.1021/acsami.1c03687
|View full text |Cite
|
Sign up to set email alerts
|

3D-Printed Submicron Patterns Reveal the Interrelation between Cell Adhesion, Cell Mechanics, and Osteogenesis

Abstract: The surface topography of implantable devices is of crucial importance for guiding the cascade of events that starts from the initial contact of the cells with the surface and continues until the complete integration of the device in its immediate environment. There is, however, limited quantitative information available regarding the relationships between the different stages of such cascade(s) and how the design of surface topography influences them. We, therefore, used direct laser writing to 3D-print submi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
35
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 26 publications
(37 citation statements)
references
References 70 publications
(165 reference statements)
2
35
0
Order By: Relevance
“…S7b), indicating the remarkable protein loading capacity of nCS. Preferable protein adsorption capacity was beneficial for the formation of focal adhesions, which was conducive to osteogenesis and vascularization [ 38 ].
Fig.
…”
Section: Resultsmentioning
confidence: 99%
“…S7b), indicating the remarkable protein loading capacity of nCS. Preferable protein adsorption capacity was beneficial for the formation of focal adhesions, which was conducive to osteogenesis and vascularization [ 38 ].
Fig.
…”
Section: Resultsmentioning
confidence: 99%
“…A Nanoscribe Photonic Professional GT laser lithography system (Nanoscribe, Germany) working on the basis of two-photon polymerization was used to fabricate the patterns. The general writing language (GWL) file of the designed pillars (diameter = 300 nm, height = 500 nm, and interspacing = 700 nm) was prepared as previously described [19,23,24]. A curable acrylate-based photosensitive resin, namely IP-L780, was polymerized under the exposure of an infrared laser beam, and submicron pillars were fabricated using a previously described protocol [22].…”
Section: Direct Co-culture Of M1s and Obs On The Patterned Surfaces 2...mentioning
confidence: 99%
“…We further investigated the influence of specific physical patterns on the response of both types of cells in the direct co-culture model established above. In our previous studies, we have extensively examined the effects of the spatial arrangement of submicron pillars on preosteoblasts [23] and macrophages [22]. Here, we studied whether submicron pillars can modulate the pro-inflammatory response observed in the co-culture towards stimulating the osteogenic response.…”
Section: Modulation Of Oim Response Via Submicron Pillarsmentioning
confidence: 99%
See 1 more Smart Citation
“…In high-throughput screening studies of surfaces consisting of needles, it was shown than only a subset of needles' features promoted the favorable polarization towards M2 macrophages from murine and human origins [14,15]. The dimensional and density aspect of the needle features was also shown to influence adhesion, mechanics, and osteogenic differentiation from murine and human cells [16][17][18]. The submicron needle-shaped surface topography feature of BCP is, therefore, pivotal for predictable fusion and should be preserved when designing bone graft formulations suitable for the end-users.…”
Section: Introductionmentioning
confidence: 99%